Clinical profile of dengue fever with severe thrombocytopenia and its complications: a retrospective study at a tertiary care hospital in South India - Kumar, Ch. Manoj; Vyas, K. S. Keerthi; Krishna, Y. Sai (International Journal of Research in Medical Sciences, 2017)
Background: Dengue haemorrhagic fever is a potentially lethal illness that is universally prevalent in the tropics and has become a major health concern globally in recent decades. The clinical manifestation of dengue infection varies from asymptomatic to severe life threatening illness in the form of DHF/DSS. Dengue haemorrhagic fever or DSS may be fatal in 40% to 50% of untreated patients. A hallmark of dengue infection is severe thrombocytopenia which causes concern for the patients and treating doctors. The objective of this study was to correlate clinical profile during the evolution of dengue fever with severe thrombocytopenia (platelets <10,000/mm3), and comparing frequencies between the different clinical forms in order to predict the severity of the disease. The present study includes 40 individuals who were found to be seropositive with the detection of NS1Ag, IgM and IgG antibodies for dengue infection with severe thrombocytopenia. Early diagnosis and monitoring is largely dependent on haematological parameters. As no specific antiviral therapy is available, supportive therapy is of utmost importance. Methods: This is an observational, descriptive and retrospective study of 40 patients with clinical and serological diagnosis of dengue fever with severe thrombocytopenia (platelets<10,000/mm3), in the period from August 2015 to September 2016, who were admitted in a tertiary care hospital in South India. ELISA was performed for the detection of dengue NS1, Ig M and Ig G, haematological parameters by automated analyzer and peripheral smear, coagulation profile analysis were done. Results: Out of 40 cases with severe thrombocytopenia, 50% of the patients had classical dengue fever, 30% cases had DHF with bleeding manifests and 20% cases with DHF plasma leakage signs and 5% lead to DSS. There was lack of association studied between severe thrombocytopenia and bleeding manifestations as p value<0.065 was insignificant. However, the risk of complications increased with decreasing platelet counts in the present study. Conclusions: Thrombocytopenia was most predominant haematological discrepancy. There was no predilection for any age group or gender for thrombocytopenia or bleeding among the dengue patients. The results were relevant in assessing the severity of infection and can help by enabling the adaptation of the therapeutic conduct to the needs of individual patients.